Valorization of red ginger hydrodistillation wastes as foot sanitizers - Puntigavere Dante; Efri Mardawati; Riska Surya Ningrum; Awaly Ilham Dewantoro; Munajat Munajat (Universitas Diponegoro, 2023)
Red ginger is known as one of the medicinnal and aromatic plants that have high value in the form of essential oils. The distillation of red ginger essential oils required large amounts of water, and then most of the water was disposed of as wastewater. This wastewater is known as hydrosol, which still contains a small amount of essential oils and secondary metabolites such as zingiberene and geraniol. These compounds were considered to have the potential to be utilized in cosmetic products such as foot sanitizers. The aim of this study was to evaluate a foot sanitizer product based on red ginger hydrosol that combined with coffee extracts based on its antibacterial activity against Staphylococcus aureus and the physical characteristics of the product. Foot sanitizer was produced in three formulations with different concentration (in percentage) of red ginger hydrosols and coffee extracts consist of F1 (45:25), F2 (35:35), and F3 (25:45). The results showed the F3 formulation provided the largest antibacterial inhibition (2.89±0.60 mm) compared to other formulations. The F3 formulation has a physical characteristics such as coffee scent aroma, a dark brown color, a pH of 5.5, a density of 960.73 kg/m3 and has a weak antibacterial activity. Based on the comparison results with previous studies, the utilization of coffee extracts in red ginger hydrosols-based foot sanitizer needs to be substitued with other natural extracts, especially having a strong antibacterial activity. It should be carried out to increase the potential value of valorizing red ginger hydrosols as foot sanitizer.